Measurement and optimization paths of the multidimensional development levels of counties in the Yellow River Basin: based on the sustainable livelihoods framework - Cheng, Lisha; Ma, Li; Qiao, Jiajun; Li, Xiaoyue (Frontiers in Environmental Science, 2024)
The Yellow River Basin (YRB) faces intense man-land conflicts. However, existing studies rarely focus on the comprehensive and multidimensional development levels in the YRB, and there is a lack of refined county-level studies, making it difficult to fully support the implementation of ecological protection and high-quality development strategy in the YRB. Under the Sustainable Livelihoods Framework, the spatial distribution, differences, and correlation characteristics of the multidimensional development levels of counties in the YRB are disclosed. This is achieved by comprehensively utilizing geospatial, socio-economic, and other multi-source data in combination with methods such as the entropy weight method, the Theil index, and spatial analysis. Optimal development paths are proposed with a focus on the development types of counties. The findings are as follows: (1) Counties in the YRB have a low overall multidimensional development level, presenting a spatial distribution pattern of “high in the east and low in the west” overall. In terms of each dimension, the average value ranking of lower reach > middle reach > upper reach is observed in each dimension; the exception is the financial dimension (with the ranking of middle reach > lower reach > upper reach). (2) Differences between counties in the development indices vary across different dimensions. The differences in the multidimensional development indices and in the development indices of each dimension (except for the natural dimension) are mainly attributable to differences between counties within each reach. Differences between reaches are non-significant. (3) The multidimensional development levels of counties in the YRB and their development levels in each dimension show strong spatial correlation. And significant counties are mainly identified as LL-type (clusters of low value areas) and HH-type (clusters of high value areas). (4) Depending on the measurement results and advantageous factors of the county multidimensional development index, counties are classified into four development types: weak development type, single-dimension-led development type, potential coordinated development type, and multidimensional coordinated development type. Based on this classification, targeted optimal development paths are proposed with a focus on the specific characteristics of different development types. The research findings can provide effective scientific support for ecological protection and high-quality development in the YRB.